Effects of a case-based interactive e-learning course on knowledge and attitudes about patient safety: a quasi-experimental study with third-year medical students - Gaupp, Rainer; Körner, Mirjam; Fabry, Götz (BMC medical education, 2016)
Background Patient safety (PS) is influenced by a set of factors on various levels of the healthcare system. Therefore, a systems-level approach and systems thinking is required to understand and improve PS. The use of e-learning may help to develop a systems thinking approach in medical students, as case studies featuring audiovisual media can be used to visualize systemic relationships in organizations. The goal of this quasi-experimental study was to determine if an e-learning can be utilized to improve systems thinking, knowledge, and attitudes towards PS. Methods A quasi-experimental, longitudinal within- subjects design was employed. Participants were 321 third-year medical students who received online surveys before and after they participated in an e-learning course on PS. Primary outcome measures where levels of systems thinking and attitudes towards PS. Secondary outcome measures were the improvement of PS specific knowledge through the e-learning course. Results Levels of systems thinking showed significant improvement (58.72 vs. 61.27; p < .001) after the e-learning. Student’s attitudes towards patient safety improved in several dimensions: After the course, students rated the influence of fatigue on safety higher (6.23 vs. 6.42, p < .01), considered patient empowerment more important (5.16 vs. 5.93, p < .001) and realized more often that human error is inevitable (5.75 vs. 5.97, p < .05). Knowledge on PS improved from 36.27 % correct answers before to 76.45 % after the e-learning ( p < .001). Conclusions Our results suggest that e-learning can be used to teach PS. Attitudes towards PS improved on several dimensions. Furthermore, we were able to demonstrate that a specifically designed e-learning program can foster the development of conceptual frameworks such as systems thinking, which facilitates the understanding of complex socio-technical systems within healthcare organisations.